Bimetallic Catalysis in Stereodivergent Synthesis. (26th September 2022) - Huo, Xiaohong; Li, Guanlin; Wang, Xi; Zhang, Wanbin
Abstract: Bimetallic catalysis has emerged as an efficient strategy for the development of new chemical reactions. Importantly, this strategy also provides a simple and powerful platform for stereodivergent synthesis, whereby all the possible stereoisomers of products bearing two stereocenters can be easily prepared from the same set of starting materials. In this Minireview, the development of stereodivergent allylic substitution, propargylic substitution, hydrofunctionalization, and annulation based on bimetallic catalysis has been summarized. It is expected that more bimetallic catalytic systems will be developed and applied for the stereodivergent synthesis of valuable molecules. Abstract : Bimetallic catalysis has emerged as an important strategy for developing new reactions in stereodivergent synthesis. This strategy is also a simple and powerful approach for synthesizing all the possible stereoisomers of products bearing two stereocenters from the same set of starting materials. This Minireview summarizes recent progress and briefly gives perspectives for the future advancement of this field.